Tessitura visual da palavra: reflexões acerca dos aspectos plásticos das palavras na obra de Mira Schendel - Marcelo de Carvalho Borges (2010)
This study addresses the relationship between word and image, trought the perspective of the visual possibilities opened by the alphabetic sign in the arts. It starts with a brief discussion about the meanings of text and image, without missing its links with the space, an common element between both. Passing by the influences of Western thought on the relationship between writing and image, the study follows with some examples on the theme in Art History, to discuss from the Barthesian concept of écriture. From this reference, the second chapter turns to the Mira Schendels work. Focusing on relevant artists production, this research draws an intertextual line between Miras selected pieces andStéphane Mallarmés and Kerlheinz Stockhausens creations. From this meeting, the study weaves a dialogue with the thought of authors such as Maurice Blanchot and Roland Barthes, on the writing status and its possibilities beyond the usual cultural conceptions. Along with the two thinkers mentioned, the discussion about the visual possibilities ofwriting resumes, but throught the point of view of their relationship with the emptiness and space. Focusing mainly on Miras artists books and monotypes, the exploration of this theme is subsidized by the theories about the origin of Chinese writing of Ernest Francisco Fenollosa as Anne Marie-Christin and their reflections on the relationship of the surface with oriental writing and with the Western alphabetic writing and thinking.